PRINSIP KESANTUNAN DALAM â€œ360 CERITA JENAKA NASRUDIN HOJAâ€ - Hafizurrahman, Hafizurrahman; Madeten, Sisilya Saman; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem which discassed in this research is obayness and disobayness of politeness principle in 360 wirty story Nasrudin Hoja by the case are . tact maxim, appbrobation maxim, agreement maxim, generosity maxim, modesty maxim, and maxim sympath. The research purpose ti descibe obayness and disobayness in politeness principle in 360 wirty story Nasrudin hoja. The beinfit of this research to add insight which related by pragmatic especialy knowing are clearly about obayness and disobayness politeness principle. Research subject is obayness and disobayness politeness principle in 360 wirty story of Nasarudin Hoja.The Method is used in this research is discriptive method. This research object is colection of wirty story Nasrudin Hoja. Date colection technich is used in this research is study documenter. Temporary date analysis whch used are model Model Miles and Huberman are reduction, supply and conclution. Based on analysys researc outcome explanitions are (1) obayness politenes principle in 360 wirty story of Nasarudin Hoja consist from nine tact maxim, two appbrobation maxim, one generosity maxim, one modesty maxim, and four agreement maxim. (2) Sympathic maxim is not obayness of politeness principle in 360 quizzical story Nasarudin Hoja. (3) Disobayness of politeness principle in 360 quizzical story Nasrudin Hoja consist from eleven tact maxim, nine appbrobation, three genorosity maxim, three agreement maxim, and sympathic maxim. (4) Modesty maxim is not in disobayness of politeness principle in 360 wirty Nasarudin Hoja.Keywords :Politeness Principle, Wirty Stor